Penyuluhan Kenakalan Remaja dan Bahaya Narkoba sebagai Bentuk Pengabdian Masyarakat dalam Program KKN di SMPN 1 Tambun Selatan - Alyssia Puteri Kirey; Bagus Pramuji; Alvy Sa’adah; Wahbi Rayhanda; Bilal Rizqy Dyas; Arnoldine Cecilia; Muhammad Fadillah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Juvenile delinquency and drug abuse are two closely related social problems that seriously threaten the moral development and future of the nation's young generation. This community service program, carried out by KKN (Community Service) students of Universitas Bhayangkara Jakarta Raya in 2026 at SMPN 1 Tambun Selatan, aims to provide education and awareness regarding juvenile delinquency and the dangers of narcotics to students. The implementation method involved preparatory coordination with the school, counseling sessions through interactive presentations, and the distribution of educational materials. The program involved 120 students from grades VII and VIII. The results show a significant increase in participants' understanding of the legal consequences of juvenile delinquency under Law No. 11 of 2012 concerning the Juvenile Justice System (SPPA), the types and dangers of narcotics under Law No. 35 of 2009, as well as motivational encouragement to maintain healthy lifestyles. This program demonstrates that structured counseling activities conducted as part of a KKN work program can serve as an effective and impactful means of community empowerment within the educational environment.